2008
DOI: 10.1634/stemcells.2007-0732
|View full text |Cite
|
Sign up to set email alerts
|

CD117-Positive Cells in Adult Human Heart Are Localized in the Subepicardium, and Their Activation Is Associated with Laminin-1 and α6 Integrin Expression

Abstract: CD117-positive cells contributing to cardiac cell turnover in normal and pathological conditions have recently been described in adult human heart. Since the precise spatial and temporal expression of extracellular matrix proteins and their receptors is critical for organ formation, we compared the distribution of cardiac primitive CD117-positive cells in the human adult normal and pathological hearts with ischemic cardiomyopathy, with respect to localization and expression of laminin and integrin isoforms. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
60
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 33 publications
7
60
0
Order By: Relevance
“…The recognition that the adult heart harbors a compartment of multipotent c-kit-positive cardiac stem cells (CSCs) (15)(16)(17)(18)(19)(20)(21)(22)(23) and other progenitor cell classes (24)(25)(26)(27)(28)(29) capable of differentiating into cardiomyocytes and coronary vessels has raised the challenging question concerning their embryologic origin and role in cardiac cell turnover and regeneration. CSCs are stored in interstitial structures with the characteristics of stem cell niches and can divide symmetrically and asymmetrically, with the ability to self-renew and form a committed progeny (17,21,30).…”
Section: Introductionmentioning
confidence: 99%
“…The recognition that the adult heart harbors a compartment of multipotent c-kit-positive cardiac stem cells (CSCs) (15)(16)(17)(18)(19)(20)(21)(22)(23) and other progenitor cell classes (24)(25)(26)(27)(28)(29) capable of differentiating into cardiomyocytes and coronary vessels has raised the challenging question concerning their embryologic origin and role in cardiac cell turnover and regeneration. CSCs are stored in interstitial structures with the characteristics of stem cell niches and can divide symmetrically and asymmetrically, with the ability to self-renew and form a committed progeny (17,21,30).…”
Section: Introductionmentioning
confidence: 99%
“…However, KIT is not a unique marker of this proposed cardiac stem cell population. KIT expression has been reported in postnatal cardiomyocytes , in adult cardiomyocytes induced to dedifferentiate (Jesty et al, 2012;Kubin et al, 2011;Zhang et al, 2010), as well as in coronary endothelial cells and epicardial cells (Castaldo et al, 2008;Limana et al, 2007;Tallini et al, 2009). KIT expression can also be induced from KIT − cells in vitro (Keith and Bolli, 2015).…”
Section: Endogenous Adult Cardiac Stem Cellsmentioning
confidence: 99%
“…6 Regarding immature cells, activation of CD117-positive cells localized in the subepicardium of adult human heart is associated with ␣6 expression. 7 Cell transplantation experiments on irradiated mice have shown that ␣6 plays a role in hematopoietic stem cell homing to bone marrow. 8 Because hematopoietic cells and endothelial cells might arise from a common precursor (the hemangioblast), we investigated the possible role of ␣6 in the homing of endothelial progenitor cells (EPCs).…”
mentioning
confidence: 99%